2018
DOI: 10.1371/journal.pone.0194773
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception increases the risk of psychotropic drug use in adolescent girls but not in adults: A pharmacoepidemiological study on 800 000 Swedish women

Abstract: The burden of depression and anxiety disorders is greater in women, and female sex hormones have been shown to affect mood. Psychological side effects of hormonal contraception (HC) are also a common complaint in the clinic, but few previous studies have investigated this subject. We therefore wanted to investigate whether use of HC was associated with adverse psychological health outcomes, and whether this association was modified by age. All women aged 12–30 years on 31 December 2010, residing in Sweden for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 39 publications
7
72
1
6
Order By: Relevance
“…First, adverse effects on mood are a known cause for discontinuation of OC use (Rosenberg & Waugh, ), potentially leading to a higher likelihood for women who are vulnerable to depression to discontinue OC use. With the common practice of combining both former and never users of OCs into one single nonuser reference group, these depression‐sensitive women would therefore be more likely to be included in the nonuser reference group (‘survivor effect’), which would result in an underestimation of a possible association between OC use and depression (Skovlund et al., ; Zettermark et al., ). Because we focus on first use of OCs rather than on current use, our study categorises comparison groups in a way that eliminates the possibility of our effects being driven by a survivor effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, adverse effects on mood are a known cause for discontinuation of OC use (Rosenberg & Waugh, ), potentially leading to a higher likelihood for women who are vulnerable to depression to discontinue OC use. With the common practice of combining both former and never users of OCs into one single nonuser reference group, these depression‐sensitive women would therefore be more likely to be included in the nonuser reference group (‘survivor effect’), which would result in an underestimation of a possible association between OC use and depression (Skovlund et al., ; Zettermark et al., ). Because we focus on first use of OCs rather than on current use, our study categorises comparison groups in a way that eliminates the possibility of our effects being driven by a survivor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent prospective population‐based analysis of over 1 million women (all women living in Denmark aged 15–34 years) indicates that, in the short term, use of OCs or other forms of hormonal contraceptives is associated with increased use of antidepressants and a higher likelihood of a first diagnosis of depression; the observed relationship was strongest in adolescents (Skovlund et al., ). In another prospective population‐based study on over 800,000 women aged 12–30 years residing in Sweden, adolescents, but not young adults, who used hormonal contraception were more likely to use other drugs commonly prescribed for mental health impairments (anxiolytics, hypnotics and sedatives) (Zettermark, Vicente, & Merlo, ). These results are further supported by two large‐scale cross‐sectional studies, which showed increased use of antidepressants (Lindberg, Foldemo, Josefsson, & Wiréhn, ) and higher rates of diagnosed depression (McKetta & Keyes, ) in adolescent OC users in bivariate associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the univariate comparisons, these models were adjusted for age, body-mass index, migration status, log-transformed values for 25(OH)D, and mean arterial blood pressure. In addition, psychotropic medication use was added to the list of confounders, since from the existing literature on adolescents, it is known that hormonal contraception increases the risk of psychotropic drug use [30]. Migration status was included as a confounder in these models, since cultural diversity is known to influence contraceptive use.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Evidencia-se a ocorrência de maior número de transtorno de ansiedade e depressão em mulheres e os hormônios sexuais femininos podem ter contribuição nesse padrão de diferenciação 7 . Tanto é perceptível essa preocupação que estudos vem sendo realizados a fim de comprovar ou descartar a associação do uso de métodos contraceptivos hormonais com efeitos adversos sobre a saúde psicológica das mulheres, a exemplo da Suécia onde um coorte maior que 800.000 participantes foram acompanhadas e comprovadas a associação, no público adolescente, de maior uso de drogas psicotrópicas após início da terapia com anticoncepcional hormonal, principalmente na população de 12 a 14 anos.…”
Section: Farley Et Alunclassified